(untitled) (Research, Society and Development, 2020)
Science Education for classes of Youth and Adult (EJA) have, in general, a very different reality in relation to other classes due to the significant adversity of the students’ socio-cultural context in relation to teaching objects, in the perspective of those who teach and those who learn. The objective of this work was to apply a proposal of an active methodology in an EJA class from a school in a city of state of Rio de janeiro. This work contributes to the improvement of teaching and learning in EJA, in addition to promoting the participation of students in this process, based on research carried out by a professor on the adoption of a methodology that approximates Dewey’s conception of applying active methods “learning by doing”. The research scenario was in a ninth grade classroom of the school. The methodological path consisted of the following steps: lesson planning, didactic sequences, didactic tools; execution of the methodological proposal; learning assessment methodology.The results obtained signaled a teaching practice that allowed students to take action, in order to experience what was being taught thus enabling an improvement in learning.